TLC optimizations of the solvent system in identification of lycopene from local watermelon (Citrullus lanatus (thunb.) Matsum. and Nakai) crude extract / Nurafiqah Shukor - Shukor, Nurafiqah (2015)
Citrullus lanatus are good source of fibre and also rich in phytonutrients namely lycopene which is believed to have the ability of reducing the risks of many disease, producing collagen and as a protection for oxidative damage because. Because of the increasing trend of lycopene estimation as one of the significant nutraceuticals for the use for food and nutritional supplements, researchers are engrossed in unindustrialized products and ingredients high in lycopene by extracting and using these compounds from Citrullus lanatus. However there are insufficient studies on the identification of lycopene compound by using column chromatography and the solvent system as the mobile phase in column chromatography to detect and identify the lycopene compound in local watermelon (Citrullus lanatus (Thunb.) Matsum. and Nakai). Therefore, this study was conducted to optimize the solvent system in the identification of lycopene by using Thin Layer Chromatography (TLC). Few solvents were used to develop the most accurate solvent system to identify lycopene compound in local watermelon (Citrullus lanatus (Thunb.) Matsum. and Nakai). Single solvent of 100% acetonitrile solvent was proved to be the best mobile phase in detection of lycopene compound by using TLC because of the polarity of the solvent. In conclusion the polarity of the solvents and the compound plays an important roles in developing a good solvent system that will produced good separations of compound